Students’ Perspectives on the Implementation of Clash of Champions Game in English Subject at STIKes Bina Cipta Husada Purwokerto - Nurhaliza, Nisrina (Journal of Education Method and Learning Strategy, 2025)
This research intended to find out students’ perspectives on the implementation of the "Clash of Champions" game in English subject at STIKes Bina Cipta Husada Purwokerto. This research was qualitative. This research was conducted on Applied Medical Laboratory Technology students of STIKes Bina Cipta Husada Purwokerto. Seven students from that study program were the subjects of this research. An open-ended questionnaire and naturalistic observation were conducted to collect the data. Then, the data was analyzed using three steps: data reduction, data display, and conclusion drawing. The result obtained that students agreed that the game gave them new experiences, glad feelings, challenge, to understand the material well, and establish solidarity among themselves. The students also can master the material well proven by the existence of a question and answer session between researchers and students at the end of the learning activity about the material given. All students can understand and apply it in everyday life. This can also answer the questions from this research.